Prevalence of haemoglobinopathies in anaemic children attending the outpatient department of paediatrics in a tertiary care hospital in Dhaka - Jui, Farjana Afroze; Anwar, S. Serjina; Khanum, Mafuza; Hasan , Saleh Mohammad Hasibul (International Journal of Contemporary Pediatrics, 2025)
Background: Anaemia in children is a significant public health issue, particularly in developing countries, where nutritional deficiencies and haemoglobinopathies contribute substantially. Understanding the prevalence and underlying causes are essential for targeted interventions. The aim of the study was to evaluate the prevalence of haemoglobinopathies in anaemic children attending a tertiary care hospital in Dhaka. Methods: This observational study was conducted over six months, from July 2024 to December 2024, at the Outpatient Department of Paediatrics in Kurmitola General Hospital, Dhaka, Bangladesh. Data were collected from children diagnosed with anaemia during study period. Demographic information, essential clinical features and laboratory findings, including haemoglobin electrophoresis and serum iron profile were analyzed to determine types of anaemia and prevalence of Haemoglobinopathies among them. Results: Out of 120 anaemic children, 71 (59.2%) were male, and 49 (40.8%) were female, with a male-to-female ratio of 1.45:1. The majority (71.7%) were aged 1–3 years. Consanguineous marriages were reported among 5.8% of the parents. Among haemoglobinopathies HbE Trait was 21.6% while Thalassemia Major, Thalassemia Minor, HbE Disease, and HbE with β-Thalassemia were 1.7%, 4.2%, 1.7% and 4.2% respectively. Iron Deficiency Anaemia (IDA) was the most prevalent condition, accounting for 50% of cases. Additionally, 16.7% of cases were due to other causes, underscoring the diverse etiology of anaemia in children. Notably, 57.5% 0f Hb E trait cases also had iron deficiency anaemia. Conclusions: Haemoglobinopathies significantly contribute to childhood anaemia, especially after nutritional deficiencies. The findings highlight the need for routine haemoglobinopathy screening and formulation of public health strategies to address genetic & nutritional causes of anaemia.